Feeling good and doing more: How does the customer respond to pro-customer deviance in the context of hospitality - Ji, Yiyu; Xu, Xiaoyan; Ji, Jingshu (Frontiers in Psychology, 2022)
Guided by the service-dominant logic, hospitality employees have to occasionally engage in pro-customer deviance to offer customized service. While pro-customer deviance has been linked with several customer attitudinal outcomes, the different customers' emotional and behavioral responses have not yet been clarified. This study explored customers' responses toward customer-contact employees and enterprises. In addition, to investigate the emotional and cognitive mechanisms underlying those response processes, this study introduced gratitude toward employee and customer–company identification as mediators in the relationship between pro-customer deviance and a series of customer extra-role behaviors. A multisource field study was conducted to test a two-stage structural equation model. The results showed that pro-customer deviance is positively related to customers' positive feedback and service friendship toward employees via gratitude. Also, the customer–company identification is found to play a mediation role between pro-customer deviance and customers' advocacy and prohibitive voice toward an organization. Theoretical and managerial contributions are also discussed at the end.